Radiation of twisted photons from charged particles moving in cholesterics - Bogdanov O. V. Oleg Viktorovich; Kazinsky P. O. Petr Olegovich; Korolev P. S. Petr Sergeevich; Lazarenko G. Yu. George Yurievich (2021, 2021)
Title screen